ASSESSMENT AND HAZARDS IDENTIFICATION ANALYSIS RISK CONTROL IN WELDING WORKSHOP SMK NEGERI 2 PEKANBARU (Al Insyirah International Scientific Conference on Health, 2021)
Hazard identification is a stage that can provide comprehensive and detailed information about the risks found by explaining the consequences of the lightest to the most severe. The purpose of this study was to determine the danger, assessment and control of risk in the Welding Workshop of SMK Negeri 2 Pekanbaru. The type and design used in this study were descriptive qualitative research with an observational approach with 4 informants. The results of the study were 13 cases that had the potential to cause danger with a high risk level of 7 cases with a percentage of 54%, moderate risk level of 2 cases with a percentage of 15%, a low risk level of 4 cases with a percentage of 31%.
Keywords: Hazard Identification; Risk Assessment; Risk Control